The Text Mining of Ethics and Information Technology - Andrej Gogora (Communications - Scientific letters of the University of Zilina, 2017)
The aim of contribution is to provide computational analysis of the journal Ethics and Information Technology by means of application of digital text mining and statistical tools on the journal‘s data extracted from 17 volumes. The procedure consists of data set building, application of various digital tools and interpretation of outputs. The analysis is conducted in order to acquire the basic topic structure of articles, to identify most frequently used terms, collocations and their occurrences with respect to the year of publishing, and to expose basic statistical author‘s data. The purpose of contribution is to present statistical overview of the journal between the years 1999 and 2016, thus to illustrate, by means of computational method, its main trends and bibliometrics data.